Aplikasi Dinoland Menggunakan Augmented Reality Untuk Pengenalan Dinosaurus Berbasis Android - Budy Satria; Sepriano; Abdussalam Al Akbar; Efitra; LM. Fajar Israwan (JSAI (Journal Scientific and Applied Informatics), 2022)
The introduction of dinosaurs that has been known to students so far is only limited to picture media in books. This is due to the absence of information media that presents information about dinosaurs ranging from shapes, sizes and moves into interactive media forms. To make an interesting learning media, it is better to make an application that is able to make learning more interesting to follow, one of which is Augmented Reality technology based on Android. This application is made using Unity, Visual Studio Code, Vuforia and Android Studio. The information on dinosaurs obtained based on the images is still limited in number such as brontosaurus, tajem, tyronosaurus and stegosaurus. Based on the results of initialization of the marker base and testing of the application, all applications run according to the stages of the research method using an incremental model.